Exploring Deep Learning Practices in Social Studies within Inclusive Elementary Classrooms: Eksplorasi Praktik Pembelajaran Mendalam IPS dalam Kelas Inklusif di Sekolah Dasar - saqjuddin, Saqjuddin; Parisu, Chairan Zibar L.; Saputra, Erwin Aksa (Jurnal Riseta Soshum, 2025)
This study aims to explore the implementation of deep learning practices in Social Studies instruction within inclusive elementary school classrooms. Within the framework of inclusive education, teachers are expected not only to deliver content but also to create learning environments that are responsive to the diverse needs of all learners. Deep learning, which emphasizes conceptual understanding, the interconnection of ideas, and real-life application, emerges as a promising approach to foster active participation among all students. This qualitative research employed a case study design involving three inclusive elementary schools in Indonesia. Data were collected through classroom observations, in-depth interviews, and document analysis. The findings reveal that deep learning practices are implemented through collaborative methods, the integration of local issues, the use of visual media, and differentiated instruction. However, several challenges were identified, including limited teacher training, administrative burdens, and inadequate resources. The study highlights the critical need for inclusive pedagogical training grounded in deep learning principles, as well as institutional support, to enhance the quality of Social Studies education in inclusive classroom settings.